Developing storytelling for tour guide to build global branding in Desa Wisata Jajar Gumregah - Dwi Wahyuningtyas; Nuriyatul Hamidah; Wahyu Kyestiati Sumarno; Azzahra Yurenaudia; Dian Sasmitha Dwi Maharani; Muhammad Rizqy Trirahardjo (Journal of Community Service and Empowerment, 2024)
Trenggalek has more than 30 tourist villages that have been intensively built since 2020, including Desa Wisata Jajar Gumregah. This village was chosen as one of the 300 best tourism villages in Anugerah Desa Wisata (ADWI) 2023. This year, one of the tourist villages proposed by the Trenggalek government was Desa Wisata Jajar Gumregah. This tourist village has much potential for development, including cultural tourism. Cultural tourism in this tourist village can be developed into storynomics tourism. To develop storynomics tourism in Desa Wisata Jajar Gumregah, the community service team from UPN “Veteran” Jawa Timur then initiated and held a program called “Storytelling for Tour Guide” in Desa Wisata Jajar Gumregah, Trenggalek. The program was successfully held on the 25th – 26th of June 2023 at Pendopo Desa Wisata Jajar Gumregah, attended by around 35 participants. They came from diverse backgrounds, from senior high school to undergraduate level. The success was proven by the participation and involvement of the participants in the discussion sessions and the publications made. In the future, the improvement of the storytelling skills of tour guides can boost the tourism sector in the area.